Literatura, história e indústria cultural em o O Xangô de Baker Street - Rocha, Renato Oliveira [UNESP]; Betella, Gabriela Kvacek [UNESP] (My University, 2012)
What seems to predominate in contemporary Brazilian literature is the presence of the cultural industry in literary production and reception. In this article we will try to discuss the concept formulated by Adorno and Horkheimer in the 1940s and how this thinking applies today in the literary field, taking as object of study the novel O Xangô de Baker Street (1995), by Jô Soares. The novel is a good example of the theory of German writers and gets new features in the industrial aspect of literature. This article focuses on the ideas and the final results of undergraduate research project supported by Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP).

O que parece predominar na literatura brasileira contemporânea é a presença da indústria cultural na produção e recepção literárias. Neste artigo, tentaremos discorrer sobre o conceito formulado por Adorno e Horkheimer na década de 1940 e sobre como esse pensamento se aplica hoje no campo literário, tomando como objeto de estudo o romance O Xangô de Baker Street (1995), de Jô Soares. O romance é um bom exemplo da teoria dos autores alemães e adquire características novas no aspecto industrial da literatura. Este artigo concentra as ideias e os resultados finais do projeto de iniciação científica apoiado pela Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP).
Keywords: Brazilian novel; Detective story; Contemporary literature; Cultural industry; Mass culture; Romance brasileiro; Romance policial; Literatura contemporânea; Indústria cultural; Cultura de massa